Advances in management accounting. Vol. 20 - Epstein, Marc J.; Lee, John Y. (Advances in management accounting,, 2012)
Volume 20 of Advances in Management Accounting is an annual publication of quality applied research in management accounting. The papers will examine areas of management accounting, including performance evaluation systems, accounting for product costs, behavioral impacts on management accounting, and innovations in management accounting. Management accounting includes all systems designed to provide information for management decision making.